Can intramuscular corticosteroid injection cause nonarteritic anterior ischemic optic neuropathy? - Bakbak B (Dove Medical Press, 2013)
Berker Bakbak, Banu Turgut Ozturk, Sansal Gedik, Bengu Ekinci Koktekir, Saban Gonul Selcuk University Medical Faculty, Department of Ophthalmology, Konya, Turkey Abstract: A 56-year-old man noted a sudden decrease of vision in his right eye 4 hours after intramuscular triamcinolone acetonide (TA) injection. A diagnosis of unilateral nonarteritic anterior ischemic optic neuropathy (NAION) was made, and the patient was counseled to discontinue using TA. Examination for possible risk factors revealed controlled hypertension. Final visual acuity was finger counting at 1 m, and the optic disc was pale in his right eye. This is the first reported case of unilateral NAION that has occurred in a patient after intramuscular corticosteroid injection. Although a cause-and-effect relationship is difficult to prove, the short duration between the TA injection and the NAION is noteworthy. The history of corticosteroid injection should be questioned in cases with predisposing conditions such as hypertension. Keywords: ischemic optic neuropathy, corticosteroids, optic disc edema